2017
DOI: 10.1515/nanoph-2017-0069
|View full text |Cite
|
Sign up to set email alerts
|

Cavity nonlinear optics with layered materials

Abstract: Abstract:Unprecedented material compatibility and ease of integration, in addition to the unique and diverse optoelectronic properties of layered materials, have generated significant interest in their utilization in nanophotonic devices. While initial nanophotonic experiments with layered materials primarily focused on light sources, modulators, and detectors, recent efforts have included nonlinear optical devices. In this paper, we review the current state of cavity-enhanced nonlinear optics with layered mat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 160 publications
(197 reference statements)
0
63
0
Order By: Relevance
“…Our SHG enhancement factor, ~7000, obtained by using WSe 2 on sapphire as a reference is only 25% of the predicted value owing to the partial absorption of the SHG signal at 400 nm by the gold substrate and partical absorption of the pump caused by the energetic proximity of the exciton in WSe 2 with pump. 12 The reabsorption of the 400-nm signal can be seen in the reflectance spectrum of gold trenches (Figure 3b). Noted that the trenches has a spectrally broad lateral gap plasmon resonance and extremely narrow mode volume thus having large electric field enhancement for pump with wavelength ranging from 800 nm to 900 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Our SHG enhancement factor, ~7000, obtained by using WSe 2 on sapphire as a reference is only 25% of the predicted value owing to the partial absorption of the SHG signal at 400 nm by the gold substrate and partical absorption of the pump caused by the energetic proximity of the exciton in WSe 2 with pump. 12 The reabsorption of the 400-nm signal can be seen in the reflectance spectrum of gold trenches (Figure 3b). Noted that the trenches has a spectrally broad lateral gap plasmon resonance and extremely narrow mode volume thus having large electric field enhancement for pump with wavelength ranging from 800 nm to 900 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we point out several prominent results in 2D materials integrated nonlinear nanophotonics. A more detailed discussion on this topic can be found out in a recent review [107].…”
Section: Nonlinear Opticsmentioning
confidence: 99%
“…In terms of third-order nonlinearity, graphene, black phosphorus, MoS 2 , and other layered materials have χ 3 susceptibility of at least the same order of magnitude with silicon [86,87]. In a silicon photonic crystal cavity covered by graphene, Gu et al observed optical bistability and self-oscillation phenomena [88] [ Fig.…”
Section: A Utilization Of Layered Materials With Parametric Nonlineamentioning
confidence: 99%